The Case for Measuring Long Bone Hemodynamics With Near-Infrared Spectroscopy - Zhang, Chuan; McCully, Kevin K. (Frontiers in Physiology, 2020)
Diseases and associated fragility of bone is an important medical issue. There is increasing evidence that bone health is related to blood flow and oxygen delivery. The development of noninvasive methods to evaluate bone blood flow and oxygen delivery promise to improve the detection and treatment of bone health in human. Near-infrared spectroscopy (NIRS) has been used to evaluate oxygen levels, blood flow, and metabolism in skeletal muscle and brain. While the limited penetration depth of NIRS restricts its application, NIRS studies have been performed on the medial aspect of the tibia and some other prominent bone sites. Two approaches using NIRS to evaluate bone health are discussed: 1) the rate of re-oxygenation of bone after a short bout of ischemia, and 2) the dynamics of oxygen levels during an intervention such as resistance exercise. Early studies have shown these approaches to have the potential to evaluate bone vascular health as well as the predicted efficacy of an intervention before changes in bone composition are detectable. Future studies are needed to fully develop and exploit the use of NIRS technology for the study of bone health.